CLINICAL AND LABORATORY DIAGNOSTICS OF TYPE 1 DIABETES MELLITUS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Type 1 diabetes is one of the most pressing health problems in the world, affecting both young people and adults. This autoimmune disease, characterized by complete or partial insulin deficiency, requires constant monitoring of glucose levels and appropriate treatment. The urgency of the problem lies in the increasing number of cases of the disease, as well as its impact on the quality of life of patients. The dangers of type 1 diabetes are not limited to just high blood sugar; it can lead to a number of serious complications, including cardiovascular disease, nephropathy and nervous system damage.